E-SATISFACTION AND CONTINUED USAGE INTENTIONS: A CASE STUDY OF LIVE SHOPPING IN INDONESIA - Chowal Jundy Kumoro; Lambok Rommy; Deni Utama; Salsabilla Khoirun Nissa (LPSDI Bina Patria, 2025)
The advancement of digital technology has driven significant changes in the e-commerce industry, particularly through live streaming e-commerce, which enables direct interaction between sellers and customers. This study aims to analyze the factors influencing continued usage behavior in the context of live streaming e-commerce in Indonesia. The research model examines the impact of Price Value, Social Influence, Online Review, Effort Expectancy, Facilitating Conditions, and Performance Expectancy on E-Satisfaction, as well as the effect of E-Satisfaction on Continued Usage Intentions and its influence on Continued Usage Behavior. This study employs a quantitative approach using a survey method, involving 250 respondents who are active users of live streaming e-commerce. The collected data is analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results reveal that all independent factors positively and significantly influence E-Satisfaction. Furthermore, E-Satisfaction strongly affects Continued Usage Intentions, which ultimately impacts Continued Usage Behavior. These findings reinforce the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) within the live streaming e-commerce context. The study provides insights for e-commerce industry players to enhance user satisfaction through competitive pricing strategies, effective customer review management, ease of platform usage, and optimal supporting infrastructure. Thus, this research serves as a foundation for businesses to improve customer retention and competitiveness in the live streaming e-commerce industry